FENOMENOLOGI PRAKTIK TAX PLANNING PADA WAJIB PAJAK BADAN - Farida, Nurul; Ludigdo, Unti; Irianto, Gugus (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2014)
Title: [The Phenomenology of Tax Planning Practice by Corporate Taxpayer]This study aims to reveal the meaning of the tax planning practice undertaken by the taxpayer. The meaning excavations carried out not only on the taxpayer, but also carried on the tax consultant. This is done because the tax consultant besides as a taxpayer also serves more than one taxpayer, so the meaning of tax planning practice undertaken by the taxpayer who obtain able much deeper. Transcendental phenomenology research method used in this study to reveal the related phenomena to the reason for the tax payers do tax planning practice. The results found that there are five reasons tax payers do tax planning practice, tax planning is permitted by the Act, the preferred business goals is to maximize the operating profit after taxes, the lack of fairness in taxation, especially in collecting tax, the existing tax system that makes taxpayer less comfortable, and the dualism obligation make taxpayers more likely to run a religious charity than pay taxes.